Design approach of mathematics learning activities in a digital environment for children with autism spectrum disorders - Santos, Maria Isabel Gomes dos (2017)
Learning environment on mathematics for autistic children is a prototype of a digital environment with dynamic adaptation features designed to offer activities towards the development of mathematical reasoning in children aged 6–12 years, diagnosed with autism spectrum disorders (ASD), a neurodevelopmental disorder characterized by deficits in social communication and social interaction as well as restricted and repetitive patterns of behaviour, interests or activities. This paper, with a primarily conceptual and analytical scope, discusses the mathematical difficulties that some children with ASD have, and presents strategies that can be used to overcome them. Based on a literature review and on the results of a preliminary study already conducted, we present results concerning the proposal of a set of learning activities for the prototype under development, specifically targeted to promote mathematical reasoning in students with ASD. Guidelines for future research are also discussed.